Práticas pedagógicas para mudanças de concepções de deficiências e atitudes sociais em relação à inclusão - Conceição, Aline de Novaes (Editora Oficina Universitária, 2022)
The book Pedagogical Practices for Changing Conceptions and Disabilities and Social Attitudes towards Inclusion represents two major contributions to the field of Education, firstly the necessary understanding of the four most common disabilities: hearing impairment, physical disability, visual impairment and intellectual disability. Secondly, the possibility of getting to know and thinking about pedagogical practices that can, with defined objectives based on the suggestions of an informative program, facilitate the development of changes in conceptions of disabilities and social attitudes towards inclusion. The main results presented by the authors, Aline de Novaes Conceição and Maewa Martina Gomes da Silva e Souza, reveal that with the application of an informative program related to inclusive pedagogical practices and didactic-methodological strategies, it is possible to constitute a harmonious and inclusive school environment .